2011
DOI: 10.1889/jsid19.12.855
|View full text |Cite
|
Sign up to set email alerts
|

A highly sensitive and low‐noise IR photosensor based on a‐SiGe as a sensing and noise filter: Toward large‐sized touch‐screen LCD panels

Abstract: Abstract— The a‐SiGe TFT photosensor for embedded touch‐screen panels (TSPs) was characterized by comparison with an a‐Si sensor. The photoresponse of an a‐SiGe sensor at a 850‐nm wavelength was much higher than that of a‐Si, indicating that a‐SiGe is a strong candidate material for an IR sensor. In order to increase the signal‐to‐noise ratio, the incident visible light was filtered by incorporating a bandpass‐filter layer. An a‐SiGe IR‐sensor‐embedded LCD panel was successfully demonstrated, showing an excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In particular, the interesting optoelectronic properties of our multilayer MoS 2 phototransistors could potentially lead to their integration into touch screen panels for flat panel or flexible display devices. Since the presence of external millimeter‐scale touch‐detecting devices (e.g., using capacitive or resistive touch sensors) in touch screen panels significantly degrades the image quality and brightness of these display devices, integration of sub‐micrometer phototransistors into touch screen panels has been suggested as a way of minimizing the degradation 11. While several semiconductors, including amorphous InGaZnO, have been reported for uses as phototransistors in touch screen panels,12 problems, such as high power consumption and reliability, remain due to their high gate bias (>10 V), high SS (>100 mV decade −1 ) and notable shift (a few V) in the threshold voltage during illumination.…”
mentioning
confidence: 99%
“…In particular, the interesting optoelectronic properties of our multilayer MoS 2 phototransistors could potentially lead to their integration into touch screen panels for flat panel or flexible display devices. Since the presence of external millimeter‐scale touch‐detecting devices (e.g., using capacitive or resistive touch sensors) in touch screen panels significantly degrades the image quality and brightness of these display devices, integration of sub‐micrometer phototransistors into touch screen panels has been suggested as a way of minimizing the degradation 11. While several semiconductors, including amorphous InGaZnO, have been reported for uses as phototransistors in touch screen panels,12 problems, such as high power consumption and reliability, remain due to their high gate bias (>10 V), high SS (>100 mV decade −1 ) and notable shift (a few V) in the threshold voltage during illumination.…”
mentioning
confidence: 99%
“…48 An in-cell touch panel using infrared sensors composed of amorphous-SiGe (a-SiGe) TFT is shown in Figure 16. 48 An a-SiGe TFT is characterized by comparison with an a-Si device. The sensing response of the a-SiGe TFT for the infrared light of the wavelength of 850 nm is much higher than that of a-Si device, indicating that the a-SiGe TFT is a strong candidate material for infrared sensors.…”
Section: Infrared Sensormentioning
confidence: 99%
“…In-cell touch panel using infrared sensors composed of a-SiGe thin-film transistor (TFT) 48 structure is shown in Figure 18. 51 The X-ray conversion structure is amorphous-Se (a-Se) film that converts Xray into electric carriers.…”
Section: Figure 16mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have been reported on the properties of aSiGe:H photosensors [6], oxide semiconductor photo TFTs [7] and a-Si photo TFTs in the near IR (NIR) regime [8], however α-Si:H touch sensors are most sensitive with respect to NIR radiation. Such properties make α-Si:H devices attractive for next generation electronics including various applications such as satellite navigation, cellular phones, matrix keyboards, electrical switchboards, and computer compatible keyboards.…”
Section: Introductionmentioning
confidence: 99%